Prevalência de cefaleia em crianças e adolescentes da cidade de São José do Rio Preto SP - Albuquerque, Regina Celia Ajeje Pires de (2009)
Several population-based studies have shown been headache as one of the most common symptoms in childhood. These have provided important consequences in headache diagnosis and treatment, since only about 11% of children with chronic headache seek medical treatment. Objectives: This study aimed at selecting a sample of school-aged children who complained headache in the last year, and to assess the headache prevalence in children and adolescents in São José do Rio Preto city (SJRP), SP. Casuistic and Methodology: A total of 5,232 children and adolescents (aged from 6 to 18 years) from SJRP randomly comprised this sample. They have been attended from the 1st to 8th grade in the year of 2004 in 13 schools: 10 public and 3 private. A questionnaire answered by parents and/or responsibles of children and adolescents was handed out in the schools to collect data. The used variables for descriptive demographic profile of the population were: age, gender, color, grade, and school for descriptive analysis of this population s demographic profile. Results: The majority was women (53.3%), white color (74.7%), and attending from the 1st to 4th grade (60%) and from the 5th to 8th grade (40%) of the elementary school. The returning of questionnaires was 61.7% in the public schools and 60% in the private. Out of the children and adolescents who have answered the questionnaire, 70% reported headache complain in the last year, only 7.2% of them did not. Out of the ones who have complained headache in the last year, 51.5% presented it occasionally during the year; 15.5%% once a month at least, 11.9% monthly and 5.2% daily. A significant difference observed in the study was regarding to the complain between the girls and the boys. More frequent headaches were reported by the girls; daily headache was twice higher than the percentile of the boys (6.6% and 3.6%, respectively). A higher headache frequency with the increase of age was observed in relation to headache and age. Our study has pointed out that headache prevalence was high in this studied population; predominantly the frequency being higher (monthly, weekly and daily) in girls and older age group.